CYCLIC CHANGES IN THE CELL SURFACE : I. Change in Thymidine Transport and Its Inhibition by Cytochalasin B in Chinese Hamster Ovary Cells - Everhart, Leighton P. (The Rockefeller University Press, 1974)
Cytochalasin B (CB) shows a marked concentration-dependent inhibition of the incorporation of [(3)H]thymidine into Chinese hamster ovary cells. This inhibition was shown to result from an inhibition of thymidine uptake, not from an inhibition of DNA synthesis. Cells normally acquire the capacity to transport thymidine as they move from the G1 stage of the cell cycle into the S phase. If CB is added to cells while they are in G1, they do not acquire the ability to transport thymidine as they enter S. However, the addition of CB to cells that are already in S has no effect on their ability to transport thymidine. These results are discussed in terms of a model in which elements involved in thymidine transport enter the cell surface membrane as the cells move from G1 to S. It is proposed that CB prevents this structural transition by binding to the cell surface.